Universal Structural Influence on the 2D Electron Gas at SrTiO3 Surfaces. Issue 22 (17th September 2021) - Guedes, Eduardo B.; Muff, Stefan; Brito, Walber H.; Caputo, Marco; Li, Hang; Plumb, Nicholas C.; Dil, J. Hugo; Radović, Milan
Abstract: The 2‐dimensional electron gas (2DEG) found at the surface of SrTiO3 and related interfaces has attracted significant attention as a promising basis for oxide electronics. In order to utilize its full potential, the response of this 2DEG to structural changes and surface modification must be understood in detail. Here, a study of the detailed electronic structure evolution of the 2DEG as a function of sample temperature and surface step density is presented. By comparing the experimental results with ab initio calculations, it is shown that local structure relaxations cause a metal‐insulator transition of the system around 135 K. This study presents a new and simple way of tuning the 2DEG via surface vicinality and identifies how the operation of prospective devices will respond to changes in temperature. Abstract : Temperature‐dependent angle‐resolved photoemission spectra of the 2‐dimensional electron gas (2DEG) formed on SrTiO3 surfaces establish that the 2DEG vanishes for temperatures close to the cubic‐tetragonal transition of the SrTiO3 surface, and that its properties also depend on the step‐edges density. The combination of experimental data with ab initio calculations reveals that the 2DEG is intimately connected to surface structural relaxations.